A PN particular solution for the radiative transfer equation in spherical geometry. (July 2017) - Garcia, R.D.M.
Abstract: A P N particular solution for the radiative transfer equation in spherical geometry is reported. A general source that varies with position and direction is considered. Abstract : Highlights: A new PN particular solution is reported. The radiative transfer equation in spherical geometry is considered. A general source that depends on position and direction is allowed.